?PREPARATION AND CHARACTERIZATION OF ACTIVATED CARBONS FROM CASHEW NUT SHELL LIQUID AND SHELLS (Biological Sciences - PJSIR, 1995)
Activatedcarbonsbasedonpolymerizedtechnicalnutshellliquid(CNSL).polymerizedcardanol.andcashew nut shells havebeenproduced andcharacterizedbynitrogenandbenzeneadsorption. Hightemperature activation to vari- ouspercentagecarbonbum-offgaveproductswhosesurfaceareasrangedbetween200and 1900m2g.1 andporevolumes between 0.12 and 0.68 mlg'. Bothsurfaceareasandpore volumesincreasewith increasein burn-off. Activation with potassium hydroxide produces the highest valuesof both surface areas and pore volumes.Cashew nut shell activated carbons are almost exclusively microporous with an average pore radius of Inm. Several analytical techniques give similar trends in the values of surface areas. pore volumesand pore radii.